Continuum-wise expansive symplectic diffeomorphisms. (January 2015) - Lee, Manseob
Abstract: We show that if a symplectic diffeomorphism is C 1 -robustly continuum-wise expansive then it is Anosov. Moreover, C 1 -generically, a continuum-wise expansive symplectic diffeomorphism is mixing Anosov.